2019
DOI: 10.1002/mus.26606
|View full text |Cite
|
Sign up to set email alerts
|

Adjusted cost analysis of video televisits for the care of people with amyotrophic lateral sclerosis

Abstract: Introduction: We previously reported our amyotrophic lateral sclerosis (ALS) video televisit experience. Here we report on video televisit versus in‐clinic costs, adjusting for perceived medical usefulness (MU). Methods: We take the patient‐perspective and a focused institutional‐perspective. Costs are adjusted for patient/caregiver and physician perceptions of visit MU. The base‐case reflects our outpatient ALS practice. Results: In the base‐case, from the patient perspective, in‐clinic visits cost $1,116 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…If patients lived closer to the institution than in the original model, savings were less, but there were still savings by using telehealth visits. The study concluded that telehealth visits provide marked adjusted cost savings for both patients and institutions under a variety of assumptions …”
Section: Synchronous Telehealth In Alsmentioning
confidence: 99%
“…If patients lived closer to the institution than in the original model, savings were less, but there were still savings by using telehealth visits. The study concluded that telehealth visits provide marked adjusted cost savings for both patients and institutions under a variety of assumptions …”
Section: Synchronous Telehealth In Alsmentioning
confidence: 99%
“…In addition, the telehealth model allows the patients to hold the consultation in familiar environments, making it more comfortable to them, maintaining the link with multidisciplinary units even in more advanced stages (46).…”
Section: Beyond the Hospital Walls Tele-health In Times Of Covid-19mentioning
confidence: 99%
“…Multidisciplinary ALS consults have been sparsely done through telemedicine, either by live videoconferences on real-time, synchronous [ [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ] or though the store-and-forward method, asynchronous [ 25 ]. Videoconferences connect the multidisciplinary ALS teams at the tertiary centres to the patients at home, or to the local community hospitals/ health centres [ 12 , 21 , 22 ].…”
Section: Already Implemented or Ongoing Studies On Emergent Technologmentioning
confidence: 99%
“…However, acute care issues were rarely discussed [ 13 ]. Adjusted cost-savings to medical usefulness of those video tele-visits as compared to in-clinic visits were further addressed [ 14 ], representing, per visit, $997 for the patients (in-clinic visit $1116; video tele-visit adjusted for medical usefulness $119) and $327 for the institution (in-clinic visit $799; video tele-visit adjusted for medical usefulness $472). Patients and providers rated medical usefulness modestly lower for video tele-visits, despite following the American Academy of Neurology Guidelines [ 26 ], as compared to in-clinic visits.…”
Section: Already Implemented or Ongoing Studies On Emergent Technologmentioning
confidence: 99%